Prototyping of manual wheelchair with alternative propulsion system. (16th November 2020) - Cavallone, Paride; Bonisoli, Elvio; Quaglia, Giuseppe
Abstract: Aim: This paper presents the study, design and prototyping of a manual wheelchair, named handwheelchair.q, with an innovative propulsion's system. The research is based on a novel system of propulsion that is more efficient and ergonomic than the hand rim one. The main goal of the designed prototype is to facilitate the mobility and to extend the reachable areas while reducing the required time. Methods: The propulsion is realised through a rowing-inspired gesture. Results: This gesture avoids the damages caused on shoulders by the compressive force of the hand rim and lever systems. Conclusion: The prototyping allowed the analysis of the project parameters and their influence on the kinematic characteristics of the prototype and the biomechanical characteristics of the gesture. The same propulsion's system can be adopted on wheelchairs devoted to sport activities, representing the starting point for a future prototype of racing wheelchairs. In this regard, the wheelchair's braking system has been redesigned in order to improve efficiency and safety. Implication for rehabilitation: The use of the Handwheelchair.q may have positive impacts in terms of the quality of life, in order to reduce the shoulder pain caused by the handrim and lever system. In addition, it can be a good tool for rehabilitation because the activity can be performed outdoor.